Rat model of anal sphincter injury and two approaches for stem cell administration - Trébol López, Jacobo; Georgiev Hristov, Tihomir; Vega Clemente, Luz; García Gómez, Ignacio; Carabias Orgaz, Ana; García Arranz, Mariano; García Olmo, Damián (My University, 2018)
AIM To establish a rat model of anal sphincter injury and test different systems to provide stem cells to injured area. METHODS Adipose-derived stem cells (ASCs) were isolated from BDIX rats and were transfected with green fluorescent protein (GFP) for cell tracking. Biosutures (sutures covered with ASCs) were prepared with 1.5 x 106 GFPASCs, and solutions of 106 GFP-ASCs in normal saline were prepared for injection. Anorectal normal anatomy was studied on Wistar and BDIX female rats. Then, we designed an anal sphincter injury model consisting of a 1-cm extra-mucosal miotomy beginning at the anal verge in the anterior middle line. The sphincter lesion was confirmed with conventional histology (hematoxylin and eosin) and immunofluorescence with 4', 6-diamidino-2-phenylindole (commonly known as DAPI), GFP and ¿-actin. Functional effect was assessed with basal anal manometry, prior to and after injury. After sphincter damage, 36 BDIX rats were randomized to three groups for: (1) Cell injection without repair; (2) biosuture repair; and (3) conventional suture repair and cell injection. Functional and safety studies were conducted on all the animals. Rats were sacrificed after 1, 4 or 7 d. Then, histological and immunofluorescence studies were performed on the surgical area. RESULTS With the described protocol, biosutures had been covered with at least 820000-860000 ASCs, with 100% viability. Our studies demonstrated that some ASCs remained adhered after suture passage through the muscle. Morphological assessment showed that the rat anal anatomy is comparable with human anatomy; two sphincters are present, but the external sphincter is poorly developed. Anal sphincter pressure data showed spontaneous, consistent, rhythmic anal contractions, taking the form of ¿plateaus¿ with multiple twitches (peaks) in each pressure wave. These basal contractions were very heterogeneous; their frequency was 0.91-4.17 per min (mean 1.6980, SD 0.57698), their mean duration was 26.67 s and mean number of peaks was 12.53. Our morphological assessment revealed that with the aforementioned surgical procedure, both sphincters were completely sectioned. In manometry, the described activity disappeared and was replaced by a gentle oscillation of basal line, without a recognizable pattern. Surprisingly, these findings appeared irrespective of injury repair or not. ASCs survived in this potentially septic area for 7 d, at least. We were able to identify them in 84% of animals, mainly in the muscular section area or in the tissue between the muscular endings. ASCs formed a kind of ¿conglomerate¿ in rats treated with injections, while in the biosuture group, they wrapped the suture. ASCs were also able to migrate to the damaged zone. No relevant adverse events or mortality could be related to the stem cells in our study. We also did not find unexpected tissue growths. CONCLUSION The proposed procedure produces a consistent sphincter lesion. Biosutures and injections are suitable for cell delivery. ASCs survive and are completely safe in this clinical setting. Key words: Fecal incontinence; Experimental rat model; Anal sphincter; Cell implantation; Cell therapy; Stem cells; Mesenchymal stem cell